SUSTAINABLE DEVELOPMENT DETERMINANTS IN THE CONTEXT OF DIGITAL TRANSFORMATION - Yulia Strilchuk; Iryna Krasnova; Serhiy Khodakevich; Ievgen Metsger; Artur Stryzhak; Andriy Dubas (Фінансово-кредитна діяльність: проблеми теорії та практики)
Progress towards sustainable development is the priority for countries all over the globe. Understanding the essence of sustainable development is a basis for conducting research and practical actions. The aim of the article is to find out the global determinants of sustainable development in the context of digital transformation. The era of digital technologies creates new approaches to solving available issues and challenges. New normality requires defining global determinants of sustainable development and creating new tools for achieving its goals. The study has provided empirical evidence and proved that ICT is one of the important drivers of sustainable development. The conducted analysis shows that there is a direct impact of ICT development and digitisation on achieving SDG 9 "Industry, Innovations and Infrastructure”. The indirect impact of digitalisation on the SDGs is analysed. It is proved that the implementation of digital technologies in business processes and digitalisation of non-IT sectors of the economy will contribute to the comprehensive implementation of a number of SDGs, such as SDGs 3, 4, 8, 9, 11, 12, and will give impetus to the achievement of other goals, which will generally have a synergistic effect. Benchmarking of practices used by well-developed countries enabled the identification of a number of priority areas related to the digitisation of the economy, namely, the development of digital skills among the population for entrepreneurial activities, state support for the digitalisation of business, especially SMEs, promotion of e-commerce, electronic payments. This study makes multiple contributions namely to academic debate on the influence of digitisation on sustainable development, demonstrates the interrelations between SDGs and highlights evidence on the global determinants of sustainable development. Conducted research outlines 4 groups of factors to enhance achieving SDGs in terms of digital transformation: 1) network coverage; 2) the number of Internet users; 3) affordability of access to the Internet; 4) digital literacy.